Proving Physical Reality and Explaining the Physical Essence of Imaginary Numbers - Antonov, Alexander Alexandrovich (European Journal of Applied Sciences, 2024)
In the article it is shown that the version of the special theory of relativity (STR), stated in all textbooks of physics, is wrong as the relativistic formulas received in it are wrong, they are incorrectly with use of wrong principle of non-exceeding of speed of light are explained and from them wrong conclusions about physical unreality of imaginary numbers and also about existence in the nature of our only visible universe are made. This generally recognized version of STR is refuted experimentally proved as a result of research of transient processes in linear electric circuits by the general scientific principle of physical reality of imaginary numbers discovered 500 years ago. It is explained that imaginary numbers in astrophysics correspond to the world of invisible parallel universes in other dimensions. Its cognition is the task of future science. However, the neighboring universes can be seen on the starry sky in portals even now. The corrected relativistic formulas are obtained and the corrected version of STR corresponding to them is created.